Develop food inks based on food waste for 3D food printing - Xiao, Tian (Nanyang Technological University, 2021)
This project aims to develop food inks base on food waste for 3D food printing—the total amount of food waste generated across the world increase steadily every year. Waste starting from agricultural products to final household consumption. Global food waste is a far-reaching issue with negative impacts on the environment, ethical and financial. Hence there must be ways to reduce it. One method is to use 3D food print to cut down waste. Food inks can be created by combining food waste with the right amount of hydrocolloids. This report aims to identify and develop food wastes into 3D printable and edible food inks. The food waste will be combined with various types and amounts of hydrocolloids to form stable ink for printing. Rheological testing will also be performed to determine the rheological properties of the inks.